Long‐term efficacy and safety of once‐monthly pasireotide in Cushing's disease: A Phase III extension study. (1st October 2019) - Fleseriu, Maria; Petersenn, Stephan; Biller, Beverly M. K.; Kadioglu, Pinar; De Block, Christophe; T'Sjoen, Guy; Vantyghem, Marie‐Christine; Tauchmanova, Libuse; Wojna, Judi; Roughton, Michael; Lacroix, André; Newell‐Price, John
Abstract: Objectives: Many patients with Cushing's disease (CD) require chronic pharmacotherapy to control their hypercortisolism. We evaluated the efficacy and safety of long‐acting pasireotide during a long‐term extension study in patients with CD. Design: Open‐label extension to a 12‐month Phase III study of long‐acting pasireotide in CD (N = 150; NCT01374906). Patients: Patients with mean urinary free cortisol (mUFC) ≤ upper limit of normal (ULN) or receiving clinical benefit at core study end could continue long‐acting pasireotide during the extension. Results: Eighty‐one of 150 (54.0%) enrolled patients entered the extension. Median overall exposure to pasireotide at study end was 23.9 months; 39/81 (48.1%) patients completed the extension (received ≥ 12 months' treatment during the extension and could transit to a separate pasireotide safety study). mUFC was ≤ULN in 42/81 (51.9%), 13/81 (16.0%) and 43/81 (53.1%) patients at extension baseline, month (M) 36 and last assessment. Median mUFC remained within normal limits. Median late‐night salivary cortisol was 2.6 × ULN at core baseline and 1.3 × ULN at M36. Clinical improvements were sustained over time. Forty‐two (51.9%) patients discontinued during the extension: 25 (30.9%) before M24 and 17 (21.0%) after M24. Hyperglycaemia‐related AEs occurred in 39.5% of patients. Mean fasting glucose (FPG) and glycated haemoglobin (HbA1c ) were stable during the extension, with antidiabetic medication initiated/escalated in some patients. Sixty‐six (81.5%) and 71 (88.9%) patients were classified as having diabetes (HbA1c  ≥ 6.5%, FPG ≥ 7.0 mmol/L, antidiabetic medication use, or history of diabetes) at extension baseline and last assessment. Conclusions: Long‐acting pasireotide provided sustained biochemical and clinical improvements, with no new safety signals emerging, supporting its use as an effective long‐term therapy for CD.